Determinants Of Expatriate Cultural Adjustment And Their Job Performance In China - Bi, Fangling (2025)
Trade globalisation forces multinational corporations (mncs) to conduct business in various geographical regions. Talent flow has emerged as one of the primary avenues for building competitive advantage among international organisations. The job performance of expatriates is crucial for mncs, as their high failure rate leads to huge financial losses. Thus, it is necessary to identify what causes the failure of overseas assignments and, subsequently, improve the expatriate’s job performance. The study’s key objective is to assess the relationship between key influential practices of expatriate management practices such as guanxi, cultural intelligence, self-efficacy, relation skills, language abilities, and cross-cultural adjustment of expatriates in china. By drawing upon cross-cultural adjustment theory and social cognitive theory, this study investigated the effect of expatriate management practices on expatriates’ job performance with facets of cross-cultural adjustment as a mediating variable. This cross-sectional study relied upon a questionnaire survey to gather data from 178 expatriates of mncs representing 54 countries. Preliminary and secondary analyses were conducted using spss and smartpls. This study reveals that guanxi and language ability positively influence all dimensions of cross-cultural adjustment, while metacognitive cultural intelligence (cq) and behavioral cq have a direct effect on general adjustment.